We are all connected: rock art ontologies in the Southwestern U.S. (3rd April 2019) - Hays-Gilpin, Kelley
ABSTRACT: Members of Indigenous communities in Arizona and New Mexico explain that petroglyphs and rock paintings serve as animate, tangible, and enduring connections among places, ancestors, and contemporary communities in ways that non-Native public lands managers can only understand with instruction in Native peoples' ontologies. Rock art sometimes takes an active role in resistance to environmental injustice and cultural appropriation. Archaeologists should study rock art in this region as material evidence for changing and varied human-land relationships, and collaborate with Indigenous communities and public lands managers to develop sustainable and culturally sensitive management programs.